Association between the -159C/T polymorphism in the promoter region of the CD14 gene and sepsis: a meta-analysis. Issue 1 (December 2017) - Wu, Qin; Xu, Xiaomeng; Ren, Jianan; Liu, Song; Liao, Xuelian; Wu, Xiuwen; Hu, Dong; Wang, Gefei; Gu, Guosheng; Kang, Yan; Li, Jieshou
Abstract Background The association between CD14-159C/T polymorphism and sepsis has been assessed but results of current studies appeared conflicting and inconstant. This analysis was aimed to determine whether the CD14-159C/T polymorphism confers susceptibility to sepsis or is associated with increased risk of death from sepsis. Method The authors conducted a comprehensive search of PubMed, EMBASE, ISI Web of Science, Cochrane library, ScienceDirect, Wiley Online Library and CNKI databases according to a prespecified protocol. Language limits were restricted to English and Chinese. Two reviewers independently selected the articles and extracted relevant data onto standardized forms. Disagreements were settled by discussion and suggestions from senior consultants. The strength of association were evaluated by odds ratio (OR) and 95% confidence interval (CI). Studies failed to fit the Hardy-Weinberg-Equilibrium were excluded. Results The research identified a total of 2317 full-text articles of which 14 articles met the predefined inclusion criteria. Meta-analysis was performed for allele frequency of C versus T, as well as genotypes CC + CT versus TT (dominant model), CC versus TT + CT (recessive model), CT versus TT and CC versus TT (additive model). All control samples were in Hardy-Weinberg proportion. No significant association between CD14-159C/T polymorphism and sepsis susceptibility or mortality were detected in the overall population. Nonetheless, subgroup analysis of Asian ethnicity revealed significant association between the CD14-159C/T polymorphism and susceptibility to sepsis in additive model (CC versus TT: OR = 0.52, 95% CI 0.29–0.92, p  = 0.03) and recessive model (CC versus CT + TT: OR = 0.50, 95% CI 0.30–0.84, p  = 0.009). Of note, three out of the five papers included in the subgroup focused exclusively on burn ICU patients. Conclusions This meta-analysis demonstrated that CD14-159C/T polymorphism is likely to be associated with susceptibility to sepsis in Asian population, especially for the TT genotype. However, bias may rise for etiologic reasons because the majority of subjects in the subgroup came from burn ICU. CD14-159C/T polymorphism is not relevant to sepsis mortality in any genetic models, regardless of the ethnicities. Due to the exploratory nature of the study, no adjustment for multiple testing was adopted, and therefore the results should be interpreted with precaution. Well-designed studies with larger sample size and more ethnic groups are required to further validate the results.